A Visual Approach to Geometric Series with Negative Ratio. (1st May 2016) - Sharif-Rasslan, Amal
Summary: An earlier visual approach for summing an infinite geometric series with positive ratios uses a book with some pages left in hand and some pages kept at each stage. We extend this book demonstration to geometric series with negative ratios by also throwing away some pages at each stage.